Cognitive control network anatomy correlates with neurocognitive behavior: A longitudinal study. Issue 2 (13th September 2016) - Breukelaar, Isabella A.; Antees, Cassandra; Grieve, Stuart M.; Foster, Sheryl L.; Gomes, Lavier; Williams, Leanne M.; Korgaonkar, Mayuresh S.
Abstract: Cognitive control is the process of employing executive functions, such as attention, planning or working memory, to guide appropriate behaviors in order to achieve a specific goal. Functional magnetic resonance imaging studies suggest a superordinate cognitive control network, comprising the dorsal regions of the lateral prefrontal cortex (DLPFC), anterior cingulate cortex (dACC) and parietal cortex (DPC). How gray matter structure changes across this network throughout neurodevelopment and how these changes impact cognitive control are not yet fully understood. Here we investigate changes in gray matter volume of the key nodes of the cognitive control network using structural MRI scans from 176 participants aged 8–38 years. One hundred and eleven of these also completed a longitudinal follow‐up at two years. We compare these with performance on a cognitive battery also measured at these two time points. We found that volume decreases in the cognitive control network were associated with improved performance in executive function (in left DLPFC and bilateral DPC), information processing (in bilateral dACC and right DPC) and emotion identification tasks (left DLPFC). These results were significant after controlling for age. Furthermore, gray matter changes were coordinated across the network. These findings imply age‐independent synaptic pruning in the cognitive control network may have a role in improving performance in cognitive domains. This study provides insight into the direct impact of structural changes on behavior within this network during neurodevelopment and provides a normative evidence base to better understand development of cognitive dysfunction in brain disorders. Hum Brain Mapp 38:631–643, 2017 . ©2016 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc.